Hybrid Plasmonic Nanostructures with Unconventional Nonlinear Optical Properties. Issue 4 (11th February 2014) - Zhang, Yong; Wang, Jing Jing; Ballantine, Kyle E.; Eastham, Paul R.; Blau, Werner J.
<x xml:space="preserve">Abstract</x> A hybrid nonlinear optical component is described based on a Au–PAA metal–dielectric assembly, which exhibits unconventional self‐defocusing and inverse optical switching behavior. This heteronanostructure realizes SPR‐induced nonlinear optics that enable an ultra‐low threshold and an extraordinarily high nonlinear response. Such an SPR‐induced nonlinear response can be further manipulated by more complex host–guest configuration such as Au–PAA–Au–C60. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>